Effectiveness of Polyethylene Glycol vs Lactulose in the Management of Functional Constipation in Children - Qayyum, Faiza; Haider, Nighat; Ambreen, Sara; Naseer, Maryam; Ejaz, Sana; Zahid, Tehmina (Biological and Clinical Sciences Research Journal, 2025)
Functional constipation is a prevalent gastrointestinal disorder in children, often leading to discomfort and reduced quality of life. Effective management is essential for timely symptom resolution and improved patient outcomes. Among the various therapeutic agents, polyethylene glycol (PEG) and lactulose are commonly used, yet comparative data on their efficacy remain limited in pediatric populations. Objectives: To compare the effectiveness of polyethylene glycol versus lactulose in the management of functional constipation in children. Methods: This quasi-experimental study was conducted at Pediatrics department of Pakistan Institute of Medical Sciences, Islamabad, Pakistan from January 2025 to May 2025. A total of 118 children with functional constipation were included, who were divided into Group-P (polyethylene glycol) and Group-L (lactulose), each containing 59 children. Diagnosis of the functional constipation in children was based on the well-validated tool named the Rome IV criteria along with the decreased number of stools (two or fewer) in a week being set as the essential criteria for making a diagnosis. Baseline characteristic including age, gender, duration of constipation, and number of stools passed each week were documented and compared between groups. Therapy was continued for a period of twelve weeks and the final assessment for the effectiveness was made after twelve weeks of therapy. The effectiveness of both these drugs was assessed based on the achievement of therapeutic success at 12-weeks and the comparison was performed between groups using the Chi-square test. Analysis of data was performed through the Statistical Package for Social Sciences (SPSS) software version 22. Results: Median age was 7.00 (5.00) years. There were 75 (63.60%) male and 43 (36.40%) female patients. Median weight was 22.00 (10.00) kg. Median duration of constipation was 2.00 (1.00) weeks. Median number of stools per week was 1.00 (1.00). Frequency of achievement of therapeutic success in Group-P (n = 59) at twelve weeks follow up was 54 (91.53%) while in Group-L (n = 59), it was 31 (52.54%), (p < 0.001). Conclusion: Polyethylene glycol is a better therapeutic option for the management of functional constipation in children as compared to lactulose.